Atraumatic multifocal intracerebral hemorrhage. (September 2016) - Fetcko, Kaleigh M.; Hendricks, Benjamin K.; Scott, John; Cohen-Gadol, Aaron A.
Highlights: Case study of atraumatic multifocal intracerebral, subarachnoid, and bilateral frontal convexity acute subdural hematomas. In the United States and Europe, intracranial hemorrhage accounts for 8–14% of all strokes. Reported incidence of multiple spontaneous intracranial hemorrhage is 0.7–3.4% of all intracranial hemorrhages. The infrequent incidence of this condition makes establishing the standard of care difficult. Abstract: This article describes a patient with atraumatic multifocal intracerebral, subarachnoid, and bilateral frontal convexity acute subdural hematomas. The patient is a 46-year-old Caucasian man who presented with a spontaneous severe progressive headache. Following a description of the case, this article reviews the reported incidence, proposed etiology, and current management strategies for multifocal spontaneous intracerebral hemorrhage.